Aboriginal Public Servants: Leadership in the British Columbia Public Service - Main, Fionna Miriam (2014)
This thesis provides preliminary, qualitative research that explores whether there is a common understanding of Aboriginal public servant leadership within the British Columbia (BC) Public Service. An interpretive, grounded theory approach underpinned by attention to Indigenous methodologies was used in this thesis. Research was conducted using semi-structured interviews with 22 self-identified Aboriginal peoples within the BC Public Service. The results identify properties of three analytical perspectives of leadership that interact in the context of Aboriginal public servants in British Columbia: (1) individual; (2) Indigenous, traditional or family setting; and (3) bureaucracy/public service. A linking theme across these analytical perspectives, “it’s personal not individual”, is proposed that influences an approach that interviewed Aboriginal public servants use in their professional positions and in their daily life. This study concludes that although there is not one specific understanding of leadership among Aboriginal public servants, their personal commitment to improving the well-being of their peoples may be the basis for their leadership work to facilitate and build bridges of understanding between communities and government. In addition, there is a call to non-indigenous public servants to consider their own leadership and share responsibility for bridge building alongside their Aboriginal colleagues. Graduate 0617 fionnamain@gmail.com